The Science of Qur’anic Readings between Narration and Understanding according to Imam al-Qastallani - Farag, Hady Hussein Abdalla; Alsaied, Mohamad Abdullah (Journal of Posthumanism, 2025)
This research addresses the integration of knowledge in the science of Qur’anic readings from the perspectives of narrative transmission (riwāyah) and analytical understanding (dirāyah). It establishes the definitions of riwāyah and dirāyah as used by scholars of Qur’anic readings in general and by Imam al-Qastallani in particular, and it reveals the most important manifestations of this integration and its impact on the scholarly formation of students of Qur’anic readings. The research follows a descriptive, inductive, and analytical methodology, as the nature of the study relies on surveying the aspects and facets of the interrelationship between riwāyah and dirāyah. The study shows the need to combine riwāyah and dirāyah, and that each of them ultimately goes back to transmitted authority. Riwāyah is a practical transmission through in-person recitation and presentation or audition (or both), while dirāyah is a scholarly transmission through texts, principles, rules, and reasoning. The study uncovers numerous indications and evidence that Imam al-Qastallani – may Allah have mercy on him – combined both riwāyah and dirāyah in the science of Qur’anic readings through his encyclopedic book Latāʾif al-ishārāt fī funūn al-qirāʾāt (“Latā’if al-Ishārāt in the Disciplines of Qirāʾāt”).